A cytomegalovirus-based vaccine provides long-lasting protection against lethal Ebola virus challenge after a single dose. Issue 19 (5th May 2015) - Tsuda, Yoshimi; Parkins, Christopher J.; Caposio, Patrizia; Feldmann, Friederike; Botto, Sara; Ball, Susan; Messaoudi, Ilhem; Cicin-Sain, Luka; Feldmann, Heinz; Jarvis, Michael A.
Abstract: Ebola virus ( Zaire ebolavirus ; EBOV) is a highly lethal hemorrhagic disease virus that most recently was responsible for two independent 2014 outbreaks in multiple countries in Western Africa, and the Democratic Republic of the Congo, respectively. Herein, we show that a cytomegalovirus (CMV)-based vaccine provides durable protective immunity from Ebola virus following a single vaccine dose. This study has implications for human vaccination against ebolaviruses, as well as for development of a 'disseminating' vaccine to target these viruses in wild African great apes.